Peran Media Sosial dalam Mempromosikan Produk UMKM - Yupiter Mendrofa; Ambrosius F.J Ndruru; Anima Halawa; Bilfret Indra Natal Lase; Indah Sari Margareth Zebua; Junita Telaumbanua; Putra Setiawan Telaumbanua; Sri Naomi Zendrato; Syukur Haryaman Telaumbanua (LPPM Universitas HKBP Nommensen, 2025)
Abstract Micro, Small, and Medium Enterprises (UMKM) play a vital role in the national economy, but often face challenges in terms of marketing and market reach. Social media offers significant potential as an effective and affordable promotional platform for MSMEs. This community service aims to analyze and demonstrate the strategic role of social media in increasing the visibility and sales of UMKM products. The methods employed include direct training and mentoring for UMKM actors on social media digital marketing strategies, pre- and post-intervention surveys, and sales impact analysis. Findings indicate that consistent and targeted utilization of social media, such as using engaging visuals and active consumer interaction, significantly increases brand awareness and sales volume of UMKM products.